Commitment to Passenger Safety in Arab Jurisdictions: الالتزام بسلامة الركاب في القوانين العربية - Mohaimen Ismael Kadhum (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Abstract Considering the expanding literature on public transportation, which covers topics as diverse as railway disruption management and electric vehicle scheduling, few people are aware of the legal frameworks that support public transportation networks. Nonetheless, such regimes are critical to successful public transportation management because they define the rights and duties of public transportation operators and passengers, with the goal of limiting passenger annoyance and injury while also improving their overall safety. We look at a key component of public transportation, namely the transporter’s dedication to passenger safety, as it is practiced in Arab countries like Egypt and Iraq. We do so by drawing on the French legal system, which has impact-ed the development of pertinent legislation in those countries substantially. Our research is qualitative and analytic in nature, and it is based on legislation, textbooks, journals, and official governmental publications. It helps to raise knowledge about the legal implications of public transportation. الملخص: بالنظر إلى الدراسات والمؤلفات المتزايدة حول النقل بشكل عام، والتي تغطي مواضيع متنوعة مثل النقل البري والنقل عبر السكك الحديدية، والغريب أن هناك قلة قليلة من الناس على دراية بالأطر القانونية التي تدعم شبكات النقل العام. ومع ذلك ، فإن مثل هذه الأنظمة ضرورية لإدارة النقل العام الناجحة لأنها تحدد حقوق وواجبات مشغلي النقل العام والركاب ، بهدف الحد من حوادث الركاب وإصابتهم مع الالتزام بسلامتهم العامة أيضًا. من هنا ينظر البحث بشكل أساس إلى عنصر في النقل البري ، ألا وهو مسؤولية الناقل في الحفاظ على سلامة الركاب ، وهذه المسؤولية تطرق إليها كلاً من المشرع في مصر والعراق. ومن ثم فإننا نقارن ذلك من خلال الاعتماد على النظام القانوني الفرنسي ، الذي أثر بشكل كبير على تطوير التشريعات ذات الصلة في تلك البلدان. بحثنا نوعي وتحليلي بطبيعته ، ويقوم على التشريعات والمجلات والمنشورات الحكومية الرسمية. يساعد على زيادة المعرفة حول الآثار القانونية للنقل البري.